Limits of life: Thermal tolerance of deep-sea hydrothermal vent copepods and implications for community succession - Alessandro Messora; Stephane Hourdez; Monika Bright; Teresa Winter; Fanny Sieler; Sabine Gollner (PLoS ONE, 2025)
Organisms that live in extreme marine environments naturally experience intermittent exposures to the limits of their physiological potential at different time scales and have developed diverse strategies to survive these variations. We tested the tolerance to thermal stress of deep-sea dirivultid copepod communities from focused and diffuse flows at East Pacific Rise 9°50’N hydrothermal vents in relation to habitat type, oxygen concentration and habitat pressure to unravel their physiological limits to extreme temperature. Lethal median time and temperature experiments were performed to derive the respective thermal death time (TDT) curves. Results showed that dirivultid copepods possess high thermal tolerance exclusively for short exposures and that in situ vent fluid flow conditions were an important predictor for maximum tolerated temperatures. Anoxia had a major negative impact on vent copepod survival, whereas atmospheric pressure did not have a significant effect. Results for the upper thermal tolerance of copepods were remarkably similar to macro- and megafauna from the same habitats, while tolerance to hypoxia or anoxia seems to increase with size. Data on relative abundance of dirivultid copepods in their habitats over the past two decades, coupled with data on temperature and anoxia tolerance, suggest that physiological limits strongly impact copepod community composition at focused flow habitats regardless of successional stage. In contrast, complex interplays of interspecific competition, food-source partitioning and experienced small-scale environmental heterogeneity within megafauna aggregations might shape dirivultid community dynamics in diffuse flow habitats.